2023
DOI: 10.3389/fimmu.2023.1189323
|View full text |Cite
|
Sign up to set email alerts
|

The role of nanotherapy in head and neck squamous cell carcinoma by targeting tumor microenvironment

Abstract: Head and neck squamous cell carcinomas (HNSCCs) refers to a group of highly malignant and pathogenically complex tumors. Traditional treatment methods include surgery, radiotherapy, and chemotherapy. However, with advancements in genetics, molecular medicine, and nanotherapy, more effective and safer treatments have been developed. Nanotherapy, in particular, has the potential to be an alternative therapeutic option for HNSCC patients, given its advantageous targeting capabilities, low toxicity and modifiabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 143 publications
(157 reference statements)
1
3
0
Order By: Relevance
“…The results demonstrate that LCNPs are suitable to deliver highly hydrophobic curcumin to HNSCC cells, independent of their HPV status, and are in line with other studies that reported good uptake of curcumin nanoparticles [38,45]. Based on the enhanced penetration and retention effect, CUR-LCNP could provide suitable accumulation inside solid tumors [46,47].…”
Section: Drug Uptake Studiessupporting
confidence: 89%
“…The results demonstrate that LCNPs are suitable to deliver highly hydrophobic curcumin to HNSCC cells, independent of their HPV status, and are in line with other studies that reported good uptake of curcumin nanoparticles [38,45]. Based on the enhanced penetration and retention effect, CUR-LCNP could provide suitable accumulation inside solid tumors [46,47].…”
Section: Drug Uptake Studiessupporting
confidence: 89%
“…One study [238] showed that MMP3 can be used as a potential biomarker for oral cancer progression. In addition, a recent study [231] found that MMP family expression correlates with the levels of infiltration of six immune cells, B cells, CD8 + T cells, CD4 + T cells, macrophages, neutrophils, and dendritic cells, suggesting that the MMP family may reflect immune status and serve as a prognostic sign in HNSCC. Kudo et al demonstrated that the highly invasive HNSCC cell line MSCC-inv1 significantly overexpresses MMP19 [239].…”
Section: Role Of the Ecm In Hnsccmentioning
confidence: 98%
“…In addition to the above-mentioned function, MMPs destroy the basal membrane and capillary wall and stimulate neoangiogenesis; therefore, these enzymes have a key role in the progression of HNSCC [227][228][229]. A number of studies have demonstrated an increase in MMPs in HNSCC [230,231]. Interestingly, the level of MMP elevation depends on the anatomical localization of squamous cell cancer in the head and neck region.. For example, MMP1 and MMP10 are highly expressed in OSCC [232] and MMP3 expression is elevated in squamous cell carcinoma of the tongue [233].…”
Section: Role Of the Ecm In Hnsccmentioning
confidence: 99%
“…[15][16][17][18] As we strive to find suitable treatment strategies in conjunction with PD-1/PD-L1 antibodies, our focus has shifted towards an emerging paradigm of targeted therapy using nanomaterials and nanotechnology, the concepts that have garnered significant attention in recent years. [19][20][21] Among these, photothermal therapy (PTT) has gained widespread acclaim as a non-invasive and highly precise cancer management method. PTT utilizes nanomaterials capable of converting light energy into heat, inducing localized hyperthermia and selectively destroying cancer cells.…”
Section: Introductionmentioning
confidence: 99%